Definitive Surgery after Neoadjuvant Chemotherapy for Locally Advanced Oral Cavity Cancers: Experience from a Tertiary Care Center - Agrawal, Mansi; Konduru, Vidya; Riju, Jeyashanth; Singh, Ashish; Joel, Anjana; Karuppusami, Reka; Tirkey, Amit Jiwan (South Asian Journal of Cancer, 2023)
Background Oral cavity cancers require definitive surgical resection as the primary treatment, but with advanced T stage, complete resection with pathologically negative margins might be difficult to achieve. Induction chemotherapy helps achieve the balance between resection and morbidity in locally advanced technically unresectable tumors. The aim of this study was to analyze the impact of surgery in locally advanced, technically unresectable oral cavity cancers after neoadjuvant chemotherapy (NACT).Materials and Methods A retrospective analysis of patients with borderline resectable, locally advanced oral cavity cancers who were given NACT between February 2017 and December 2021 was conducted. Data regarding clinical and pathological characteristics, NACT, surgery, adjuvant therapy, and recurrences was analyzed.Results Of the 69 patients in the study, 69.6% had tongue cancer, rest were gingivobuccal complex cancers. All tumors were resected based on the post-NACT tumor volume and clear margins were achieved in 42% of cases. About 85.4% of the tongue cancers required a lesser resection than anticipated, thereby following the concept of organ and functional preservation post-NACT as proposed by Licitra et al. About 30.4% had ypT0 and 17.4% had ypN0. Recurrence and survival rates noted in our study were comparable to those reported in literature. Lymph node density of more than or equal to 0.07 was found in all recurrent cases.Conclusions Induction chemotherapy offers a chance of achieving adequate surgical resection while reducing morbidity and improving functional outcomes for patients with technically unresectable oral cavity cancers. Nodal disease may not respond to chemotherapy as well as the primary tumor. There is a need for comprehensive evaluation of prognostic factors, which could help identify the patients who will most benefit with NACT.
Keywords: oral squamous cell carcinoma; neoadjuvant chemotherapy; induction chemotherapy; oral cavity cancer; NACT; borderline resectable oral cancer; technically unresectable cancer